2019
DOI: 10.3389/fncel.2019.00233
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Pro-inflammatory Effect of Downregulated CD73 Expression in EAE Astrocytes

Abstract: CD73, an ectonucleotidase, participates in the regulation of immune responses by controlling the conversion of extracellular AMP to adenosine. In this study, we investigated whether any type of brain cells, especially neuroglia cells, exhibit altered CD73 expression, localization or activity upon experimental autoimmune uveitis (EAU) induction and whether altered CD73 manipulates the activation of effector T cells that interact with such cell types. First, the amount of cell membrane-exposed CD73 was detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…Interestingly, a pro-inflammatory effect of CD73 downregulation in EAE astrocytes was recently demonstrated. In this study, CCPA showed the same effect as Ado on CD73 −/− astrocytes, while other selective AR agonists did not [64].…”
Section: The Beneficial Role Of a 1 Ars In Autoimmunitysupporting
confidence: 44%
“…Interestingly, a pro-inflammatory effect of CD73 downregulation in EAE astrocytes was recently demonstrated. In this study, CCPA showed the same effect as Ado on CD73 −/− astrocytes, while other selective AR agonists did not [64].…”
Section: The Beneficial Role Of a 1 Ars In Autoimmunitysupporting
confidence: 44%
“…This phenomenon was observed not only in peripheral immune cells but also in glial cells in the CNS. Recent studies have demonstrated that genetic removal of astrocytic CD73 blocks AMP-mediated cytokine release from astrocytes [ 258 ]. Badimon et al [ 16 ] recently showed that microglial CD39/CD73-mediated ATP hydrolysis suppresses neuronal activity by activating A 1 adenosine receptor (A 1 R) in a feedback regulatory manner.…”
Section: Introductionmentioning
confidence: 99%
“…7a – e ), or CD73 ( Fig. 4a ), which is expressed by striatal microglia, albeit at levels lower than in striatal neurons, as judged by CD73 mRNA and protein expression 18 , 25 , 35 ( Fig. 4b , Extended Data Fig.…”
mentioning
confidence: 99%